Vulcanization, centrifugation, water-washing, and polymeric covering processes to optimize natural rubber membranes applied to microfluidic devices - Cabrera, Flavio C. [UNESP]; Dognani, Guilherme [UNESP]; Faita, Fabricio L.; Santos, Renivaldo J. dos [UNESP]; Agostini, Deuber L. S. [UNESP]; Bechtold, Ivan H.; Crespilho, Frank N.; Job, Aldo E. [UNESP] (Springer, 2016)
Natural rubber microfluidic devices are based on the replication of microchannels and chambers through the casting of latex and combine the flexibility and transparency of the polymeric platform. Natural rubber is a proposed alternative material to prepare microfluidic devices, owing to the advantages of flexibility, eco-friendliness, and lower cost compared to other commonly used polymeric microfluidic materials. However, the challenges for the use of natural rubber are the leaching of compounds when it is in contact with fluids, the low stretching resistance, and the decreases of transparency rate in terms of the water absorption rate. To overcome these issues, we report the evaluation of the essential mechanical, optical, and structural properties of natural rubber for centrifuged and pre-vulcanized rubber membranes, as well as the polymeric coating over the membrane surfaces. We propose the centrifugation process for decreasing the leach composition of the natural rubber platform and vulcanization to improve the mechanical resistance of the polymeric membrane devices. The polymeric coating prevents the leaching of compounds from natural rubber membranes and water absorption without significant reduction in transparency or increase in the hydrophobicity of the surface. Once the centrifuging, vulcanization, and coating processes improve the rubber properties, this polymer will become an alternative flexible and low-cost material for microfluidic technology.